Geochemistry of drill core headspace gases and its significance in gas hydrate drilling in Qilian Mountain permafrost. (February 2015) - Lu, Zhengquan; Rao, Zhu; He, Jiaxiong; Zhu, Youhai; Zhang, Yongqin; Liu, Hui; Wang, Ting; Xue, Xiaohua
Highlights: Headspace gases with higher gas concentration are indicative of gas hydrate. Headspace gases are mainly thermogenic source. Gases geochemistry indicates migration along or across faults or fracture zones. Abstract: Headspace gases from cores are sampled in the gas hydrate drilling well DK-8 in the Qilian Mountain permafrost. Gas components and carbon isotopes of methane from headspace gas samples are analyzed. The geochemical features of the headspace gases along the well profile are compared with occurrences of gas hydrate, and with the distribution of faults or fractures. Their geochemical significance is finally pointed out in gas hydrate occurrences and hydrocarbon migration. Results show high levels of hydrocarbon concentrations in the headspace gases at depths of 149–167 m, 228–299 m, 321–337 m and 360–380 m. Visible gas hydrate and its associated anomalies occur at 149–167 m and 228–299 m; the occurrence of high gas concentrations in core headspace gases was correlated to gas hydrate occurrences and their associated anomalies, especially in the shallow layers. Gas compositions, gas ratios of C1 /ΣC1–5, C1 /(C2 + C3 ), iC4 /nC4, and iC5 /nC5, and carbon isotopic compositions of methane (δ 13 C1, PDB‰) indicate that the headspace gases are mainly thermogenic, partly mixed with biodegraded thermogenic sources with small amounts derived from microbial sources. Faults or fracture zones are identified at intervals of 149–167 m, 228–299 m, 321–337 m, and near 360–380 m; significantly higher gas concentrations and lower dryness ratio were found in the headspace gases within the fault or fracture zones compared with areas above these zones. In the shallow zones, low dryness ratios were observed in headspace gases in zones where gas hydrate and faults or fracture zones were found, suggesting that faults or fracture zones serve as migration paths for gases in the deep layers and provide accumulation space for gas hydrate in the shallow layers of the Qilian Mountain permafrost.